Expected Returns and Habit Persistence - Li, Yuming (Review of Financial Studies, 2001)
Using a consumption-based asset pricing model with infinite-horizon nonlinear habit formation, Campbell and Cochrane (1999) show that low consumption in surplus of habit should forecast high expected returns. This article argues that the finite-horizon linear habit model also implies an inverse relation between expected returns and surplus consumption. This article also presents empirical evidence, which indicates that expected returns on stocks and bonds vary with surplus consumption implied by the habit models. The volatility of returns and the reward to volatility are also related to surplus consumption. However, less than 30% of the predictable variation of expected returns, using standard lagged information variables, is attributed to surplus consumption. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.